ONLINE CLASSROOM DENGAN PEMANFAATAN K12LESSONPLANS BAGI GURU-GURU SMP. H. ISRIATI SEMARANG - Sri Wahyuni; Laily Nur Affini; Th. Cicik Sophia B (Universitas PGRI Semarang, 2013)
This society service is carried out using a free teacher website;www.k12lessonplans.com, in a form of training for teachers at SMP. H.Isriati Semarang. There are 15 teachers joining this training, which is heldon 14 ?óÔé¼ÔÇ£ 16 July, 2012, starting from 09:00 am - 02:00 pm. This trainingtakes place in the Computer Laboratory group and individual audience isconducted consecutively from 17 ?óÔé¼ÔÇ£ 21 July, 2012 and 23 ?óÔé¼ÔÇ£ 26 July startingfrom 02:00 ?óÔé¼ÔÇ£ 04:00 pm in the teachers?óÔé¼Ôäó longue at the school. This programis aimed to give the teachers knowledge and training, to implement onlineclassroom using the website. The methods used in this program are;explanation, question and answer, training and group guidance.Key words: online classroom, teacher website, k12lessonplans